2010
DOI: 10.1063/1.3378674
|View full text |Cite
|
Sign up to set email alerts
|

Design of a laser-assisted tomographic atom probe at Münster University

Abstract: To benefit from the latest technical improvements in atom probe analysis, a new tomographic atom probe has been built at the University of Münster, Germany. The instrument utilizes a femtosecond laser system with a high repetition rate combined with the ability of using a micrometer-sized extraction electrode and a wide angle configuration. Since field evaporation is triggered by laser pulses instead of high-voltage pulses, the instrument offers the ability to expand the range of analyzed materials to poorly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…First APT results on the elemental distribution in Cu(In,Ga)Se 2 layers, which are similar to CIS, were recently published by Cadel et al [15] and Schlesiger et al [16]. Both authors reported significant sodium enrichment at the grain boundaries.…”
Section: Introductionmentioning
confidence: 56%
“…First APT results on the elemental distribution in Cu(In,Ga)Se 2 layers, which are similar to CIS, were recently published by Cadel et al [15] and Schlesiger et al [16]. Both authors reported significant sodium enrichment at the grain boundaries.…”
Section: Introductionmentioning
confidence: 56%
“…APT analyses were performed in a local electrode APT built at the University of Münster 30 . Thermally induced field evaporation was performed with fs pulses from a ultraviolet laser (l ¼ 343 nm, 200 kHz, 30 nJ pulse À 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A new instrument dedicated to the analysis of complex materials was developed and put into operation at university of Muenster recently [27]. Meanwhile, first measurements of relevant battery materials were tested.…”
Section: Atom Probe Tomographymentioning
confidence: 99%